Pemanfaatan Ekstrak Daun Sungkai (Peronema canescens Jack) Untuk Menurunkan Kadar Asam Lemak Bebas Dan Bilangan Peroksida Dalam Minyak Jelantah - Elis Ulfa; Selpi Dollangi (Universitas Lancang Kuning, 2023)
Used cooking oil has a high level of free fatty acids (FFA) and peroxide numbers caused by oxidation processes. One of the efforts to lower the levels of free fatty acids and peroxide numbers by adding natural antioxidants from sungkai leaf extract (Perorena Canescens Jack). Sungkai leaf extract contains several secondary metabolite compounds such as alkaloids, flavonoids, phenolics, steroids and saponins which have the potential to be natural antioxidants. This study aims to determine the ability of sungkai leaf extract to reduce the level of free fatty acids and peroxide numbers in used cooking oil and find out the concentration of sungkai leaf extract which is effective in reducing the level of free fatty acids and the number of peroxides in used cooking oil. In this study, sungkai leaf extract was varied in concentration, namely 0.25%, 0.5%, 0.75% 1%, and 1.25% of the mass of used cooking oil used. Used cooking oil is heated using a hotplate for 15 minutes at 80°C and stirred using a magnetic stirrer at a rate of 200 rpm, stored for 3 days and filtered using filter paper. The results showed that sungkai leaf extract can reduce levels of free fatty acids and peroxide numbers in used cooking oil. The best results were obtained at a concentration of sungkai leaf extract of 1.25% w/v with a free fatty acid content of 1.25% and a peroxide number of 10.45 meq O2/kg.